2002
DOI: 10.1002/eat.10021
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder symptomatology is not associated with pregnancy and perinatal complications in a cohort of adolescents who were born preterm

Abstract: These results indicate that traumatic episodes early in life, including brain insults, do not appear to increase the susceptibility of developing eating disorder symptomatology, depression, deficiency of self-esteem, or distortion of body shape during late adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…14,15 Only 25% of the LBW girls perceived themselves as overweight, compared to 42-43% in populations of same aged girls in general. 9,16 The results on eating attitudes are consistent with findings from one small prospective study 4 that examined eating attitudes among 24 prospectively followed prematurely born girls and found no relation between common LBW birth complications and the development of unhealthy eating attitudes at 18-19 years of age. Together, these findings suggest that LBW per se is not a risk factor for abnormal eating attitudes in adolescent girls and would not be useful to include in a screen to identify girls at high risk for eating disorders.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…14,15 Only 25% of the LBW girls perceived themselves as overweight, compared to 42-43% in populations of same aged girls in general. 9,16 The results on eating attitudes are consistent with findings from one small prospective study 4 that examined eating attitudes among 24 prospectively followed prematurely born girls and found no relation between common LBW birth complications and the development of unhealthy eating attitudes at 18-19 years of age. Together, these findings suggest that LBW per se is not a risk factor for abnormal eating attitudes in adolescent girls and would not be useful to include in a screen to identify girls at high risk for eating disorders.…”
Section: Resultssupporting
confidence: 90%
“…1,3 Furthermore, the research has almost exclusively focused on clinical populations and can thus not be generalized to how nonreferred LBW girls feel about their weight and eating. The one study that examined eating attitudes in nonhospitalized LBW girls 4 found no connection between LBW and abnormal eating attitudes, but the sample size was too small to draw a firm conclusion. This study fills a gap in the literature by examining the prevalence of disturbed eating attitudes and weight concerns in a large prospective regional sample of LBW girls.…”
Section: Introductionmentioning
confidence: 94%
“…Increased risk of anorexia nervosa (AN) was associated with being born at less than 32 weeks' gestation (Cnattingius, Hultman, Dahl, & Sparen, 1999) and lower gestational age (Foley, Neale, & Kendler, 2000). However, participants were aged between 18 and 19 years and therefore not completely over the period of risk for ED (Feingold, Sheir-Neiss, Melnychuk, Bachrach, & Paul, 2002). In contrast to these investigations, a small prospective study did not find a higher prevalence of ED in preterm adolescents.…”
Section: Introductionmentioning
confidence: 92%
“…11,[14][15][16][17] Muscle strength may also be reduced, 18 although differences become less apparent as teens get older. However, some studies of ELBW and VLBW survivors in late teens and early adulthood found no height or weight differences 19,20 with catch-up growth to puberty in ELBW 16 and VLBW children. 21 Various studies have also shown that small for gestational age ELBW infants who did not experience catch-up growth throughout childhood remained smaller as adults, 21 with 1 study finding that small for gestational age VLBW boys show the least catch-up growth.…”
mentioning
confidence: 98%